Structured growth of zinc oxide nanorods on plastic optical fiber and light side coupling towards sensing applications / Hazli Rafis Abdul Rahim - Hazli Rafis, Abdul Rahim (2017)
A simple and cost effective optical fiber sensor using side coupling of light into the core modes of plastic optical fiber (POF) coated with zinc oxide (ZnO) nanorods is reported here. Nanorods coating enhanced coupling inside the fiber by scattering light but were also capable of causing leakage. Structuring the growth to specific regions allowed scattering from different segments along the fiber to contribute to the total coupled power. A uniform, densed and highly aligned spiral patterned ZnO nanorods were grown on the POF using the hydrothermal method and its effect was investigated. ZnO nanorods growth time of 12 h and temperature of 90 °C provided the best coupling voltage. Side coupling was measured to be a factor of 2.2 times better for spiral patterned coatings as opposed to unpatterned coatings. The formation of multiple segments was used for multiple-wavelength channels excitation where different bands were side coupled from different segments. It was found that visible white light source significantly coupled the light into the POF compared with infrared laser sources. A first order theoretical model was derived to simulate the impact of millimeter (mm) scale spiral patterns on coupling efficiency by varying the width and spacing of the coated and uncoated regions. The width of spiral patterned ZnO nanorod coatings on POF was optimized theoretically for light side coupling and was found to be 5 mm. An experimental validation was performed to complete the optimization and the experimental results showing a well correlation with simulation. Optimized width of spiral patterned ZnO nanorods grown on large core POFs was used for the purpose of temperature and multiple optical channel alcohol vapor sensing. Spiral patterned ZnO nanorods coating exhibited a significant response to temperature change from 20 ˚C to 100 ˚C based on extinction concept which is the attenuation of light by scattering and absorption as it traverses the ZnO nanorods. Sensitivity was measured to be a factor of 1.3 times better for spiral patterned coatings as opposed to unpatterned coating. The multiple optical channel alcohol sensing mechanism utilized changes in the output signal due to adsorption of methanol, ethanol and isopropanol vapors. Three spectral bands consisting of red (620-750 nm), green (495-570 nm) and blue (450-495 nm) were applied in measurements. The range of relative intensity modulation (RIM) was determined to be between 25 to 300 ppm. Methanol presented the strongest response compared to ethanol and isopropanol in all three spectral channels. With regard to alcohol detection RIM by spectral band, the green channel demonstrated the highest RIM values followed by the blue and red channels respectively.